SAPI PERAH (SATU PION PENJELAJAH SEJARAH) SEBAGAI MEDIA PEMBELAJARAN IPS SEJARAH HINDU BUDHA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDN SAMIRONO YOGYAKARTA - Rahmani Hakim, Latifa Dinar; Pangestu, Dimas Aldi; Andini, Ghina (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
This research aims to (1) to find out the application of Sapi Perah learningmedia to the grade IV SDN Samirono, (2) to find out the process of learning history ofHinduism and Buddhism through the use of Sapi Perah learning media, and (3) toreveal the improvement of the understanding and learning ability of grade IV studentsof Samirono Elementary School. The method used is classroom action researchinvolving two cycles. In the first cycle, the students were given a description of thehistory of Hinduism and Buddhism. Then, they were given a pre test on the materialthat has been taught and tried to apply the Sapi Perah learning media. However, theresults were not satisfying because they were not enthusiastic in learning. The secondcycle was conducted by applying the learning media of Sapi Perah again. In the secondcycle optimal results were obtained. The students’ learning outcomes of the history ofHinduism and Buddhism improved. The results of this research are (1) the applicationof a learning media Sapi Perah can improve the students’ understanding of the historyof Hinduism and Buddhism and (2) the learning process in the classroom becomesmore interesting because of the use of the media of Sapi Perah.